Patent ductus venosus presenting with cholestatic jaundice in an infant with successful trans-catheter closure using a vascular plug device - Anith Chacko (Indian Journal of Radiology and Imaging, 2016)
Persistent ductus venosus as a cause of cholestatic jaundice is very rare. Treatment varies, but is usually reserved for infants in whom complications develop. We report a 5-week-old female infant with cholestatic jaundice caused by a patent ductus venosus and subsequent successful treatment via a transcatheter occlusion using a vascular plug device.